Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang di Kawasan Objek Wisata Garuda Wisnu Kencana (GWK) - Herdina Selviani Tamba; Ni Nyoman Reni Suasih (Jurnal Visi Manajemen, 2024)
The high number of visitors to GWK as one of the tourist attractions in Badung district is believed to have a multiplier effect on the surrounding community from increasing community income. One of the indicators of welfare is income. This means that the higher the income, the higher the opportunity to meet the living needs of the community. Income is the amount of money or economic value earned by individuals, households, or other entities from various sources in a given period of time. This study aims to 1) to analyze the influence of capital, business duration, working hours and location simultaneously on traders' income in the Garuda Wisnu Kencana tourist attraction area, South Kuta. 2) to analyze the influence of capital, business duration, working hours and location partially on the income of traders in the Garuda Wisnu Kencana tourist attraction area. This research was conducted in Revayah Plaza, Badung Regency. The respondents in this study were 82 traders with a sampling method using the Nonprobability Sampling technique. The data analysis technique used in this research is multiple linear regression. Top of FormThe results of this r state that 1) Business capital, business duration, working hours and trading locations simultaneously have a significant positive effect on the income of traders in the Garuda Wisnu Kencana (GWK) tourist attraction area, especially in Revayah Plaza. 2) Business capital partially has a positive and significant effect on traders' income; Partially, the income of traders with strategic trading locations tends to be higher than traders with non-strategic trading locations; The income of traders with working hours ≥ 40 hours per week tends to be higher than traders with working hours < 40 hours per week in the Garuda Wisnu Kencana (GWK) tourist attraction area, especially in Revayah Plaza. Meanwhile, the duration of partial business has a negative and insignificant effect on the income of traders in the Garuda Wisnu Kencana (GWK) tourist attraction area, especially in Revayah Plaza.Bottom of Form